Teacher Career Development Management at Madrasah Aliyah Negeri - Syafaruddin Syafaruddin; Mesiono Mesiono; Indrasyah Sitompul (STAI Hubbulwathan Duri, 2021)
This study aims to analyze the management of teacher career development at MAN 2 Model Medan. The research focuses on planning, organizing, implementing, and evaluating teacher career development at MAN 2 Model Medan. This study uses a qualitative approach with a descriptive-analytical study method. Obtaining data using observation techniques, interviews, and document studies. Furthermore, the data were analyzed using data reduction techniques, data presentation, and drawing conclusions or data verification. The results of this study indicate that the management of teacher career development at the MAN 2 Medan Model is carried out effectively. It can be viewed from the aspects; (1) planning for teacher career development in the form of motivation and application of a conducive organizational culture (climate); (2) organizing human resources (HR) for teachers in madrasah through leadership support, technical meetings, coordination between madrasah leaders and vice-principals involving supervisors to improve teacher qualifications; (3) the implementation of teacher career development is carried out based on promotion, transfer, and promotion; (4) evaluation of teacher career development is carried out based on online-based supervision and teacher performance assessment. This research hopes that it can be used as a reference for further research on the management of teacher career development in Islamic educational institutions. This research also has implications for teachers in Islamic educational institutions to accelerate careers as educators in madrasah.